Analisis Rancangan Sistem Monitoring Posisi Hewan Menggunakan Lora - Muhammad Afdhaluddin; Ilsa Palingga (Journal of Information System Research (JOSH), 2023)
For some people, having a pet can relieve stress or fatigue. There are also people who raise animals to supplement their income. Animals such as cats, cows and goats are animals that are often found in settlements and areas. Usually these animals are released in apartments. Of course, once released, the owner will no longer be able to control his pet. That's why we need a device to control these pets. Based on the above information, it is necessary to have technology that is focused on surveillance systems. This technology uses surveillance devices based on the Internet of Things (IoT). The task of the monitoring device is to retrieve and collect data from the environment being measured. There are main components such as Arduino Nano 328P, NodeMCU ESP8266, LoRa, Ublox NEO-6M Gps and Android. This system has two tools, a transmitter and a receiver. First, the transmitter sets up a TET connection. When the connection is stable, the base station's GPS recovers local information in the form of longitude and latitude. After the data is successfully retrieved, the data is stored and the location is sent to the recipient (LoRa). After receiving the data (LoRa), the receiver will set up the connection first, when the connection is stable, the data received from the transmitter will be sent to the server and displayed on the App. The tool works well at a maximum distance of ±35 meters and if the tool works at a distance of 25-35 meters the coordinate point is still legible but not accurate. If the tool works more than 40 meters then the coordinates will not be read at all. The distance and position of the transmitter can affect the results on the display in the Blynk application and the coordinate points on the Arduino.